再概念化：課程改革的邏輯與實踐Reconceptualization: the Logic and Praxis of Curriculum Reform - 許芳懿Fang-Yi Hsu (Journal of Curriculum Studies, 2006)
「再概念化」起源自1970年代的再概念化運動，由William Pinar所發起。「再概念化」本身意喻著「不斷的重新定義」，代表一種批判、省思與重定位。我國的九年一貫課程改革立意在學習者中心，發展結果卻偏向菁英主義，顯示其邏輯與實踐存有矛盾。本文針對我國當前課程改革進行檢視，檢視角度除蘊含再概念化的歷史變化觀點外，更擷取「再概念化」內在的批判精神來檢驗九年一貫課程，針對統整、基本能力、鬆綁解構、國家教育目標等結構性問題提出質疑，同時亦探討績效責任、社會公平、倫理向度、文化同質性、工具理性問題，文末並提出省思與結論。 “Reconceptualization” stemmed from the “reconceptualization movement” initiated by Pinar in 1970s.“Reconceptualization” means “constant redefinition” which represents criticism, reflection and re-focus. Curriculum reform lately in Taiwan focused on learner centered, but it was inclined to elitism finally. That represents the relation between the logic and practice of curriculum reform was contradictory mutually. The article was aimed to review the reform of grades 1st–9th integrative curriculum lately in Taiwan. It was not only from the viewpoints of the history of reconceptualizaton, but includes the inner essence of criticism. The structural problems of integration, basic ability, deconstruction and the aims of country education were suspicious. Simultaneously, the accountability, social justice, ethic, cultural homogeneity, instrumental rationality were explored. Finally, the reflection and conclusion were suggested.